The development of Moringa leaves effervescent granules with effervescent agent of citric acid and sodium bicarbonate - Karina Citra Rani; Nani Parfati; Nikmatul Ikhrom Ekajayani; I Made Abdi Kurniawan; Ni Putu Wangi Kristiani (Pharmaciana, 2021)
Moringa leaves are part of Moringa Oleifera, which have a high antioxidant content, therefore, it is beneficial for overcoming free radicals in the body. Furthermore, the leaves contents have the potential to be developed into a functional drink in the form of effervescent granules. The important aspects influencing the physical characteristics, stability, and acceptability of granule is the type and ratio of the effervescent agent. In this study, citric acid and sodium bicarbonate were used as effervescent agents because they both provide acceptable texture and mouthfeel. This study aimed to develop an effervescent granule formula of Moringa leaves and to optimize the molar ratio of citric acid and sodium bicarbonate as the effervescent agent. Three molar ratios of citric acid and sodium bicarbonate were optimized, namely 1:3.11 (Formulation 1), 1:3 (Formulation 2), and 1:2.93 (Formulation 3). These formulations were developed using the wet granulation method. The results showed effervescent granules of the three formulations exhibited good flowability and uniform particle size distribution. Furthermore, formulation 3 showed better granule flow characteristics than the others. The results after reconstitution showed the granules were quickly dispersed within 207-234 secs, the pH of the preparation ranged between 5.74-5.92 (neutral pH), the viscosity was between 326-333 cps, and exhibited dilatant flow characteristics. Also, the organoleptic and sensory evaluation results showed formulation 3 was the most acceptable in terms of color, taste, aroma, and texture. Based on these findings, it was concluded that formulation 3 which used (citric acid ratio, sodium bicarbonate 1:2.93) was the optimal formulation.